2019
DOI: 10.1002/wer.1134
|View full text |Cite
|
Sign up to set email alerts
|

Level and distribution of nutrients in the hyporheic zone of Lake Taihu (China) and potential drivers

Abstract: To better understand the nutrient distributions in the hyporheic zone of a large shallow eutrophic lake (Lake Taihu) and the potential drivers, the total organic carbon (TOC), total nitrogen (TN), and total phosphorus (TP) were investigated in March and December 2016. Spatial differences in the TN and TP contents existed in the hyporheic zone, particularly between the eastern and southern zones and the western and northern zones. The TOC/TN ratios in the western, northern, and central zones were mostly <8 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
2
2
0
Order By: Relevance
“…This leads to an alternating upwelling and downwelling hyporheic flow at the eastern sites. These flow patterns in the nearshore hyporheic zone also agree with those reported earlier by Li et al [40,50] on the basis of nutrient-and chloride-depth profiles.…”
Section: Hyporheic Flow Pattern Analysissupporting
confidence: 92%
See 3 more Smart Citations
“…This leads to an alternating upwelling and downwelling hyporheic flow at the eastern sites. These flow patterns in the nearshore hyporheic zone also agree with those reported earlier by Li et al [40,50] on the basis of nutrient-and chloride-depth profiles.…”
Section: Hyporheic Flow Pattern Analysissupporting
confidence: 92%
“…Naranjo et al [24] reported from a large oligotrophic sub-alpine lake, Lake Tahoe (USA), that groundwater discharge are temporally variable due to seasonal changes in recharge within the watershed, wave action, and lake stage, and groundwater discharge was enhanced by the seasonally-low lake stage and episodic recharge caused by precipitation falling as rain in the watershed. The temporal changed hyporheic flow patterns verified in this study also agreed well with other studies [28,29,40], reporting that the sediment of Lake Taihu spatial-temporally served as a source or sink of nutrients.…”
Section: Hyporheic Flow Pattern Analysissupporting
confidence: 91%
See 2 more Smart Citations